2005
DOI: 10.1097/01.rct.0000157472.98277.5c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Gadolinium-DTPA on Diffusion-Weighted Magnetic Resonance Images for Evaluation of Focal Hepatic Lesions

Abstract: There was no significant difference before and after administration of contrast agent in the SNR or CNR of DWI. This indicates the feasibility of postcontrast DWI as a substitute for an unsuccessful precontrast-enhanced study in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
4
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 22 publications
2
43
4
2
Order By: Relevance
“…Although a previous study demonstrated the feasibility of enhanced DWI in liver MRI using gadopentetate dimeglumine (Gd-DTPA) [15], the effects of Gd-EOB-DTPA on DWI or the measured ADC have not been examined. Unlike extracellular contrast agents such as Gd-DTPA, approximately 50% of the injected dose of Gd-EOB-DTPA is specifically taken up into hepatocytes [12,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Although a previous study demonstrated the feasibility of enhanced DWI in liver MRI using gadopentetate dimeglumine (Gd-DTPA) [15], the effects of Gd-EOB-DTPA on DWI or the measured ADC have not been examined. Unlike extracellular contrast agents such as Gd-DTPA, approximately 50% of the injected dose of Gd-EOB-DTPA is specifically taken up into hepatocytes [12,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…On the postmortem T1WI, the unwashed contrast was still observed, but the existence of contrast agent did not affect the postmortem ADC value in this study, because research has shown that the magnetic susceptibility of contrast medium should not influence the ADC value (34,35).…”
Section: Discussionmentioning
confidence: 79%
“…Some studies have indicated that without reaching statistical significance, Gd-EOB-DTPA can influence DWI and T2-weighted images by causing higher magnetic susceptibility and T2 shortening [23,24]. In general, the DHBP with Gd-EOB-DTPA is acquired about 20 min after contrast administration, because at this time normal hepatocytes reach maximum signal intensity [25].…”
Section: Discussionmentioning
confidence: 99%